Patricia Highsmith : her diaries and notebooks, 1941-1995 - Highsmith, Patricia, 1921-1995 (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2021)
"Publishing for the centenary of her birth, Patricia Highsmith's diaries "offer the most complete picture ever published" of the canonical author (New York Times). Relegated during her lifetime to the pulpy genre of mystery, Patricia Highsmith has emerged since her death in 1995 as one of "our greatest modernist writers" (Gore Vidal). Presented for the first time, this one-volume assemblage of her diaries and notebooks-posthumously discovered behind Highsmith's linens and culled from more than 8,000 pages by her devoted editor, Anna von Planta-traces the mesmerizing double-life of an artist who "[worked] like mad to be something." Beginning in 1941 during her junior year at Barnard, the diaries exhibit the intoxicating "atmosphere of nameless dread" (Boston Globe) that permeates classics such as Strangers on a Train and the Ripley series. In her skewering of McCarthy-era America, her prickly disparagement of contemporary art, her fixation on love and writing, and ever-percolating prejudices, the famously secretive Highsmith reveals the roots of her psychological angst and acuity. In one of the most compulsively readable literary diaries to publish in generations, at last we see how Patricia Highsmith became Patricia Highsmith"--